A case of non-neutropenic invasive pulmonary aspergillosis under immune checkpoint inhibitor therapy for malignant melanoma. (2022) - Uchida, Yoshinori; Shimamura, So; Ide, Shuichiro; Masuda, Kazuki; Saiki, Masafumi; Sogami, Yusuke; Ishihara, Hiroshi
Abstract: The patient was a 70-year-old man with diabetes mellitus, alcoholic liver disease and bronchial asthma treated with corticosteroid and long-acting β-agonist inhalants. He had also been treated with nivolumab for advanced malignant melanoma for two years with a partial response. He presented to our department with intractable cough, which was attributed to uncontrolled bronchial asthma. Two weeks later, he presented with a high fever and worsened cough. He was diagnosed with bacterial pneumonia based on severe inflammation revealed by laboratory tests and right upper lung consolidation on chest radiography. Antibiotics via either oral or parenteral administration were ineffective and no pathogen was detected in sputum or blood cultures. Based on the air-crescent sign observed on chest computed tomography and a diffuse pseudomembranous lesion on the airway epithelium that was observed via bronchoscopy along with positive serum Aspergillus antigen, a clinical diagnosis of invasive pulmonary aspergillosis (IPA) was made and liposomal amphotericin B was initiated. Three days later, the patient developed massive hemoptysis, and he died of respiratory failure. Later, aspergillus-like mycelia were observed in the pathology of bronchial biopsy, supporting the clinical diagnosis of IPA. Although the use of immune checkpoint inhibitors has been reported to be beneficial for patients with some infectious diseases, it does not seem to be the case for patients with other infectious diseases including our patient.